The Implementation of TQM in Higher Education Institutions in Saudi Arabia: Marketing Prospective (Global Journal of Management and Business Research, 2017)
This research aimed to reveal the extent of the implementation of total quality management (TQM) in higher education institutions in Saudi Arabia in light of the perceptions of the educational and administrative leaders. A questionnaire have been developed consisting of (70) items distributed in eight areas of TQM. The research applied to a sample of 135 leaders from the educational and administrative leaders in Qassim University. The results of the research showed that the application of the principles of total quality management in higher education institutions in Saudi Arabia was medium from the standpoint of administrative leaders with the exception of the area of Academic Affairs and the field of community service where its application was high. The application of the principles of Total Quality Management was medium from the standpoint of educational leaders with the exception of the area of strategic planning.
Keywords: quality; total quality management; higher education; leadership